Molecular determinants of substrate specificity in the efflux pump CraA from Acinetobacter baumannii - Wuen Ee Foong; Xinxin Xiang; Klaas M. Pos; Heng-Keat Tam (Microbiology Spectrum)
ABSTRACT The major facilitator superfamily (MFS) type efflux pumps of Acinetobacter baumannii play important roles in antibiotic resistance. However, the molecular mechanism of these transporters remains poorly understood. To address the molecular basis of substrate polyspecificity mediated by multidrug MFS transporters, we compared the substrate binding modes of A. baumannii CraA with its well-studied homolog, Escherichia coli MdfA. MdfA and CraA share similar structural features, including a cavity accessible to drugs from the cytoplasm when these transporters adopt the inside-out conformation. This predominantly hydrophobic cavity contains several distinct titratable and hydrophilic residues. Through substitution analysis, we demonstrate that these polar residues within the CraA drug binding cavity contribute to the transport of all tested drugs, whereas mutations of hydrophobic residues result in altered drug recognition profiles. In addition to the known titratable residues E38 and D46, we identified E338 as the only titratable residue that plays a substrate-specific role, as it is required for efficient transport of norfloxacin, but not ethidium. Substitution of E338 with asparagine or glutamine changes substrate specificity, enabling specific recognition of phenicols and mitomycin C. Furthermore, we show that the aromaticity of Y42 is crucial for phenicol recognition, while general hydrophobicity at this position is critical for mitomycin C specificity. We propose that E338 and Y42 function as key substrate selectivity determinants in CraA.IMPORTANCEMultidrug efflux transporters of the major facilitator superfamily (MFS) are key contributors to antibiotic resistance, mediating the export of structurally diverse compounds across bacterial membranes. While homologous transporters such as Escherichia coli MdfA and Acinetobacter baumannii CraA share high structural similarity and overlapping substrate profiles, the molecular basis of their substrate specificity remains poorly understood. In this study, we show that structural homology among MFS transporters does not inherently imply mechanistic conservation, as species-specific variations can give rise to distinct substrate recognition profiles. Our findings reveal that CraA utilizes unique residues Y42 and E338 for substrate selectivity, while R124 and Y73 contribute to its transport activity. These findings enhance our understanding of efflux pump specificity and underscore the need to consider organism-specific features when targeting multidrug transporters in antimicrobial therapy.